Efek Daun Etlingera hemisphaerica pada Perbaikan Skoring Spermatogenesis Tikus Putih (Rattus norvegicus) yang Diinduksi HgCl2 - Liya Agustin Umar; Siti Habiburrahmah Ash Shadar; Kartika Sari; Hilda Taurina; Marisadonna Asteria; Aceng Ruyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of administration of Etlingera hemispharica leaf extract on white rats (Rattus norvegicus) induced by mercury chloride as seen from the histopathological description of the testes. The research method used is experimental post-test-only control group design. The extract was administered for seven days by gavage. Testicular organ harvesting was carried out on the 9th day after the rats were euthanized and continued with making testicular preparations. Testicular damage was assessed using the Johnsen score. Data were analyzed using non-parametric statistical tests. The results showed that the test groups had a p-value of 0.000. The histopathological description of the testes induced by HgCl2 had a p-value of 0.005 and the administration of E. hemisphaerica leaf extract in HgCl2-induced mice showed a p-value of 0.008. In conclusion, administration of E. hemisphaerica leaf extract to R. norvegicus induced by mercury chloride improved spermatogenesis on the histopathological features of the R. norvegicus testes. Keywords: Etlingera hemispharica, HgCl2, Johnsen Score, Rattus norvegicus